State dissolution, sovereign debt and default: Lessons from the UK and Ireland, 1920-1938 - Nathan Foley-Fisher; Eoin McLaughlin (Queen's University Centre for Economic History (QUCEH), 2014)
We study Irelands inheritance of debt following its secession from the United Kingdom at the beginning of the twentieth century. Exploiting structural differences in bonds guaranteed by the UK and Irish governments, we can identify perceived uncertainty about fiscal responsibility in the aftermath of the sovereign breakup. We document that Irelands default on intergovernmental payments was an important event. Although payments from the Irish government ceased, the UK government instructed its Treasury to continue making interest and principal repayments. As a result, the risk premium on the bonds the UK government had guaranteed fell to about zero. Our findings are consistent with persistent ambiguity about fiscal responsibility far-beyond sovereign breakup. We discuss the political and economic forces behind the Irish and UK governments decisions, and suggest lessons for modern-day states that are eyeing dissolution. "Further, in view of all the historical circumstances, it is not equitable that the Irish people should be obliged to pay away these moneys" - Eamon De Valera, 12 October 1932
Keywords: N23; N24; G15; 330; state dissolution; sovereign default; Irish land bonds; Dublin Stock Exchange